Peran Ekonomi Syariah dalam Mendorong Inklusi Keuangan: Meningkatkan Akses dan Kesejahteraan - M.Arief Safii; Fauzatul Laily Nisa (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
. This study reviews the role of Islamic economics in promoting financial inclusion through literature analysis. Through a comprehensive review, we evaluate the concept of financial inclusion, Islamic economic principles, and the contribution of Islamic financial institutions to financial inclusion. The results showed that the Islamic economy plays a significant role in increasing public access to financial services by developing products and services in accordance with Islamic principles. Principles such as the prohibition of usury and the equitable sharing of risks serve as the foundation for financial products and services that are more inclusive and sustainable. Institutions such as Islamic banks, Islamic microfinance institutions, and Islamic capital markets have an important role in reducing financial disparities and increasing public access to financial services. Nevertheless, challenges such as low levels of Islamic financial literacy and unsupportive regulations remain obstacles to Islamic economic development and financial inclusion. Therefore, further steps are needed to improve Islamic financial literacy, strengthen supportive regulations, and encourage innovation in Islamic financial products and services.